2008
DOI: 10.20452/pamw.306
|View full text |Cite
|
Sign up to set email alerts
|

Vasculopathy and vasculitis in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disease, where vascular lesions are one of the typical symptoms. The pathological process often involves skin vessels, renal glomeruli, the cardiovascular system, brain, lung alveoli, and gastrointestinal tract vessels. This review presents possible adverse mechanisms underlying the cause and effect relationship of various factors causing vascular lesions in SLE patients. The generally accepted hypothesis links vascular damage in SLE with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 36 publications
0
44
0
8
Order By: Relevance
“…6,7 Recent studies on lupus vasculitis and nephritis showed that activated monocytes and macrophages vigorously participate in, and amplify inflammation, which influences the outcome of the condition. [33][34][35] In these experiments, transwell chambers were used to detect the effect of IC-pretreated CRL-1730 cells and the transendothelial migration of U937 cells as compared with negative control CRL-1730 cells.…”
Section: Monocyte Transendothelial Migration Is Enhanced By Pretreatmmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Recent studies on lupus vasculitis and nephritis showed that activated monocytes and macrophages vigorously participate in, and amplify inflammation, which influences the outcome of the condition. [33][34][35] In these experiments, transwell chambers were used to detect the effect of IC-pretreated CRL-1730 cells and the transendothelial migration of U937 cells as compared with negative control CRL-1730 cells.…”
Section: Monocyte Transendothelial Migration Is Enhanced By Pretreatmmentioning
confidence: 99%
“…6,7 Vasculopathy and vasculitis could be associated with the deposition of ICs on endothelium, leading to endothelial cell activation and inflammatory cell infiltration into the inflammatory sites. [6][7][8][9] However, the effects of ICs on endothelial cells and the potential mechanisms involved remain unclear.…”
mentioning
confidence: 99%
“…Również częściej występują zmiany skórne w postaci siności siatkowatej (livedo reticularis), ponadto niedokrwistość, przyspieszone OB oraz często stwierdza się obecność przeciwciał anty-SS-B [19]. Epizod zapalenia naczyń może się rozwinąć na skutek odkładania się kompleksów immunologicznych w ścianie naczynia, ale również wskazuje się na rolę przeciwciał przeciwko komórkom śródbłonka (antiendothelial cell antibodies -AECA), które prowadzą do ich bezpośredniego uszkodzenia [21]. Obecność przeciwciał AECA stwierdza się nawet u 80% chorych na TRU [22].…”
Section: Zajęcie Naczyńunclassified
“…[14]. Vascular disease in SLE patients can occur due to a combination of diferent pathological processes, for example, atherosclerosis, cloting disorders, and systemic vasculitis associated with vascular wall injury (especially endothelial dysfunction), caused by an autoimmune process [24,28].…”
Section: Introductionmentioning
confidence: 99%
“…SLE patients most typically exhibit cutaneous vasculitis; systemic vasculitis develops in 10-18% of these patients and, as a life-threatening condition, may require aggressive therapy [14,15].…”
Section: Introductionmentioning
confidence: 99%